Research Culture of Russian University Students - P. A. Ambarova; N. V. Shabrova; E. V. Kemmet; A. N. Mikhailova (Moscow Polytechnic University, 2023)
The article is devoted to the summarizing results of the sociological study of the re- search culture of students (February-April 2023, n=3,032 people). The aim of the article was to iden- tify its features and contradictions in the conditions of modern Russian universities. The productivity of the theoretical and methodological framework for studying this problem, developed on the basis of L.N. Kogan's approach, is argued. The article proposes to consider the research culture as a way of developing the essential forces of students and to identify its structural elements such as cognitive, axiological and praxeological. In accordance with the theoretical and methodological approach, the characteristic of the research culture of students is given. The results of the survey allowed us to conclude that the majority of students have an interest in science and scientific knowledge as values, and at the same time - about the formation of a critical assessment of the risks that research produces among students who are active in scientific terms. The problem areas of students' research competencies that prevent the "seamless" integration of student and "adult" science, including meth- odological and organizational ones, have been identified. Such problematic features of the praxe- ological block of students' research culture as their low involvement in publication practices and tol- erance to unethical research practices are shown. The significant influence of teachers and scientific mentors performing activating and socializing functions on the formation of the research culture of students is substantiated. The practical significance of the research lies in a comprehensive under- standing of the state of the research culture of students of Russian universities, identifying factors that influence (positively or negatively) its formation and development. On this basis, it is possible to develop scientifically based programs for the academic development of students, especially in terms of its scientific track.